Growth performance of planted Shorea roxburghii in degraded area at Ayer Hitam Forest Reserve, Selangor - Darus, Nor Aznida (2018)
The enrichment planting has been found to be an effective technique for rehabilitation of forest. However, not many species are able to withstand adverse weather condition at the planting area and information on growth performance of Shorea roxburghii planted under different canopy is still lacking. This study was carried out on a degraded area at Ayer Hitam Forest Reserve, Puchong Selangor to evaluate the growth performance and survival rate of S. roxburghii under different shadings. The line planting technique was applied with planting distance of 2 m × 2 m both in Plot A (Open area) and Plot B (Shaded area). The studies showed that S. roxburghii recorded the higher survival percentage in Plot A compared to Plot B. For diameter increment, trees in Plot A recorded bigger diameter increment at 1.80 mm compared to trees in Plot B (1.10 mm) for the seven month period. In term of height increment, Plot A showed a larger value (9.00 cm) than height increment in Plot B. There was no significant difference (p>0.05) in height and diameter increment between Plots A and B. The study showed that S. roxburghii recorded better growth performance under open area and the species can be considered as a species to be applied in enrichment planting in degraded areas. Rehabilitation or enrichment planting helps to restore the productivity of planted forest in terms of biological parameters.